Storage network enhancement - Lim, Seth Yew Siong. (2012)
The volume of data that storage centers are handling is rising exponentially. This is due to increasing dependency by IT executives, trying to avoid rising infrastructural costs, subscribing to the services of technologies such as data storage centers.